The criminal mind. - O'Hanlon, Charlene (New York ACM, 2006)
We're all vulnerable to cybercrime.
Keywords: Computing Milieux; Computers and Society; Public Policy Issues; Abuse and crime involving computers; Management of Computing and Information Systems; Security and protection; Invasive software (e.g. viruses, worms, trojan horses).